'Because we are not apart, we are a part': an interview with Vandana Singh. Issue 3 (3rd July 2022) - Baishya, Amit R.
ABSTRACT: This interview with science fiction writer Vandana Singh focuses on her rapidly expanding oeuvre in climate fiction. More specifically, she discusses her cli-fi under the umbrella of three major concerns: their realist settings in a near future, the affirmative depiction of technology as agent, and the representation of climate as a complex system. While the interview focuses largely on Singh's cli-fi forays, it places these recent efforts within her career trajectories as both a noted science fiction writer and a professor of physics at Framingham State University. Besides discussing the politics and aesthetics of her stories that encompasses both humans and nonhumans, the interview also discusses how her pedagogy shapes her imaginative engagements with climate change and the geological epoch of the Anthropocene.